Visible but Hidden: An Intersectional Examination of Identity Management Among Sexual Minority Employees - Dhanani, Lindsay Y.; Totton, Rebecca R.; Hall, Taylor K.; Pham, Carolyn T. (Journal of Management, 2024)
As organizations have increasingly prioritized the inclusion of sexual minorities, there has been a proliferation of studies examining the ways by which organizations can foster environments that enable sexual minorities to express themselves authentically at work. Yet, extant research has predominantly ignored the role of other social identities in shaping the experiences of sexual minority employees, their decisions regarding the ways they express their sexual identities at work, and the consequences of those decisions. The current study correspondingly draws on theorizing on intersectionality to propose that workplace experiences related to race, a visible identity, may alter the decisions employees make about the expression of their invisible sexual identities. We additionally extend current conceptualizations of identity management to consider the ways employees may manage the presentation of their more visible racial identities at work. Results indicated that harassment experienced on the basis of sexual orientation and race combined to influence identity management strategies related to sexual and racial identities. Furthermore, concealing one's sexual orientation and suppressing one's racial identity uniquely contributed to decrements in employee well-being and interacted to predict employee outcomes. Yet, the nature of the interactions varied by employee race. Findings from this study support the need to adopt an intersectional approach to understanding invisible inequalities at work and inform future theoretical and practical efforts aimed at fostering workplace inclusion. Keywords: identity management; sexual orientation; race; employee well-being